2023
DOI: 10.3389/fevo.2023.1218149
|View full text |Cite
|
Sign up to set email alerts
|

Potentially differential impacts on niche overlap between Chinese endangered Zelkova schneideriana and its associated tree species under climate change

Abstract: Climate change has a significant impact on the potential distribution for endangered trees. However, to date, little is known about how the endangered trees and main associated ones in different types of subtropical forests respond to climate change. Here, we first selected the endangered Zelkova schneideriana endemic to China and its associated trees as focus species from two subtropical forest communities (i.e. deciduous broad-leaf forest, bamboo and broad-leaf mixed forest) in China, and divided them into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 70 publications
3
17
0
Order By: Relevance
“…Among all climate variables, Bio6 (minimum temperature of the coldest month) and Bio2 (mean diurnal temperature range) have the greatest impact on the distribution of Zelkova schneideriana . This finding aligns with Zhou et al’s previous study [ 23 ]. Zhou et al suggested that the ample precipitation in subtropical regions is unlikely to be a limiting factor for the distribution of Zelkova schneideriana .…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Among all climate variables, Bio6 (minimum temperature of the coldest month) and Bio2 (mean diurnal temperature range) have the greatest impact on the distribution of Zelkova schneideriana . This finding aligns with Zhou et al’s previous study [ 23 ]. Zhou et al suggested that the ample precipitation in subtropical regions is unlikely to be a limiting factor for the distribution of Zelkova schneideriana .…”
Section: Discussionsupporting
confidence: 94%
“…Over time, the distribution range of Zelkova schneideriana in both climate scenarios is expected to face contraction, consistent with previous findings [ 23 , 26 ]. In subtropical regions of China, variations exist in the trends of changes observed in plant distribution areas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The model predicts the species’ fundamental niche rather than the actual niche, resulting in the predicted potential distribution area being larger than the actual range. However, the species may fail to disperse to some suitable areas due to biogeographical barriers, such as human interference, topographical obstacles, and inter-specific competition 49 .…”
Section: Discussionmentioning
confidence: 99%